Media and social capital - Filipe R. Campante; Ruben Durante; Andrea Tesei (Queen Mary University of London, School of Economics and Finance, 2021)
We survey the empirical literature in economics on the impact of media technologies on social capital. Motivated by a simple model of information and collective action, we cover a range of different outcomes related to social capital, from social and political participation to interpersonal trust, in its benign and destructive manifestations. The impact of media technologies hinges on their content ("information" vs "entertainment"), their effectiveness in fostering coordination, and the networks they create, as well as individual characteristics and media consumption choices.
Keywords: D71; D72; D74; D83; D84; Z13; 330; Social capital; media; collective action; information; coordination; participation